EARLY AID SOCIALIZATION IN EMERGENCY FOR COMMUNITY LEADERS IN RW 6 KELURAHAN KEMAYORAN - Maria Theresia Arie Lilyana; Kristina Pae (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Health education to the community is carried out to increase knowledge insight, so that it is expected to know and be able to provide assistance to trauma and emergency conditions encountered in the community. The activity will be held on October 3, 2021 at the RW 6 Kemayoran Village, Krembangan District. The activity was attended by 20 participants consisting of RT heads and community leaders in the area. The results of the activity showed that before the provision of health education, 4 people had scores below 60 points and 16 participants scored above 60. The scores obtained after health education were 2 people with scores below 60 points and 18 people scored above 60 points. Based on these data, this activity is able to increase the knowledge of the general public. This activity should be carried out on an ongoing basis so that it has a real impact and provides benefits for increasing awareness of the general public so that they know and are able to provide assistance in trauma and emergency conditions.